Financial Performance and Banking Stock Prices: The Effects of CAR, NPL, ROA, and LDR on Indonesian Listed Banks, 2018–2022 - Cintya Sarah Leanita; Retno Suliati Suleiman (Golden Ratio of Data in Summary, 2026)
This causal study examines the effects of the Capital Adequacy Ratio (CAR), Nonperforming Loan ratio (NPL), Return on Assets (ROA), and Loan-to-Deposit Ratio (LDR) on the stock prices of banking companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sample comprises 200 firm-year financial statements from 40 companies selected through purposive sampling over a five-year period. Data were analyzed using statistical software through classical assumption testing, the simultaneous F-test, partial t-tests, the coefficient of determination, and multiple linear regression. The results show that CAR, NPL, ROA, and LDR jointly have a significant effect on banking stock prices. Partially, NPL has a significant negative effect, indicating that higher nonperforming loans reflect deteriorating asset quality and greater credit risk, which may weaken bank profitability, reduce investor confidence, and depress stock prices. ROA has a significant positive effect, indicating that stronger earnings generated from total assets provide a favorable signal to investors. By contrast, CAR and LDR do not have significant partial effects on stock prices. Nevertheless, both ratios remain important in the broader context of capital resilience, liquidity management, cash flow, and bank sustainability.